Successful outcomes of surgery procedures in patient with Glanzmann´s Thrombasthenia - Guerrero Arismendiz, Bruno Renato (2023)
We report a 35-year-old female patient with Glanzmann's thrombasthenia (GT) and severe anemia due to abnormal uterine bleeding secondary to uterine myomatosis. She required several admissions of red blood cells and platelet transfusions. An elective subtotal hysterectomy with salpingo-oophorectomy was proposed and recombinant factor VII was required. Surgical and postoperative outcomes were successful, without surgical complications, bleeding, or hemogram alterations. 4 years later, she required tooth extraction because of periodontal disease and pulp necrosis. In Peru, reports of GT patients requiring major and minor surgical procedures are lacking, given the low disease prevalence and the difficulties related to surgery. The report of these successful cases becomes relevant to continue improving GT management.